Kyā Weda ilahāmī haiṃ? : "Weda" nāmī dharama pusatakāṃ de anādi, ananta, ate īshwara krita hoṇa para ika nirapakkha khoja - Sewā Siṅgha, 1882-1945 (SAMP early 20th-century Indian books project ;)
Critique on Vedas.